2018
DOI: 10.2147/ccide.s193326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total occlusal convergence on fit and fracture resistance of zirconia-reinforced lithium silicate crowns

Abstract: IntroductionComputer-aided design (CAD) and computer-aided manufacturing (CAM) monolithic crowns are gaining momentum. Limited evidence exists about the effect of tooth preparation total occlusal convergence (TOC) on marginal and internal gap distances in addition to load to fracture values.AimThe aim of this study was to evaluate, by microcomputed tomography (µCT), the influence of 12° and 20° TOC on marginal and internal adaptation of zirconia-reinforced lithium silicate (ZLS) crowns. Moreover, values of loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
3
12
1
1
Order By: Relevance
“…When using natural teeth, the researcher can perform various bonding techniques that have a significant influence on the behavior of the materials being investigated. 37,38 In in-vitro studies, the dentin wetness, thickness and the pressure of the tooth pulp are influential variables that try to imitate in-vivo conditions. The modulus of elasticity of natural teeth is essential factor when applying fracture tests as the other materials do not behave as natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…When using natural teeth, the researcher can perform various bonding techniques that have a significant influence on the behavior of the materials being investigated. 37,38 In in-vitro studies, the dentin wetness, thickness and the pressure of the tooth pulp are influential variables that try to imitate in-vivo conditions. The modulus of elasticity of natural teeth is essential factor when applying fracture tests as the other materials do not behave as natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 crowns were thus fabricated for marginal and internal fit evaluation: Group 1, 16 monolithic Zi crowns; Group 2, 16 monolithic ZLS crowns (n = 16). The sample size of this study was based on earlier related published studies [ 25 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Based on the mean differences and standard deviation assumptions, the total sample size was estimated as 24 crown samples (12 for each of the two ‘ceramic material’ groups), at α = 0.05 and power of 85% (G* Power statistical power software v.3.1.9.7) for the marginal and internal gap evaluations.…”
Section: Methodsmentioning
confidence: 99%
“…The results hence rejected the hypothesis described in the introduction. Alammari et al [34] reported that an increase of TOC (from 12 to 20 degree) did not affect marginal and internal fit but resulted in higher load to fracture values of ceramic crowns. A similar finding was reported by Corazza et al [35], who compared the influence of 6 • , 12 • , and 20 • TOC on the fracture load of yttria partially stabilized zirconia veneered with feldspathic porcelain.…”
Section: Discussionmentioning
confidence: 99%